Electrocatalytically inactive copper improves the water adsorption/dissociation on Ni3S2 for accelerated alkaline and neutral hydrogen evolution. Issue 4 (20th January 2021) - Zhang, Lei; Gao, Xiaorui; Zhu, Ying; Liu, Acan; Dong, Huilong; Wu, Dajun; Han, Zhida; Wang, Wei; Fang, Yong; Zhang, Jie; Kou, Zongkui; Qian, Bin; et al.
Abstract : Electrochemically inactive Cu was introduced into Ni3 S2  nanoparticles to accelerate its Volmer step and strengthen water adsorption/dissociation on the respective Ni and S sites during the HER process, leading to superior HER performances. Abstract : Nickel dichalcogenides, especially Ni3 S2, present inferior alkaline and neutral hydrogen evolution activity due to their sluggish water dissociation kinetics. Although these materials hold promise as non-noble metal-based electrocatalysts for the hydrogen evolution reaction (HER) in acidic media, developing efficient strategies to enhance the water dissociation processes of nickel dichalcogenides in alkaline and neutral solutions is also an important area of research. The present work discloses an electrocatalytically inactive copper doping strategy to promote the water adsorption and dissociation process of Ni3 S2 (Cu-Ni3 S2 ) nanoparticles supported on nickel foam (NF) towards improving the alkaline and neutral hydrogen evolution reactions. Based on combined density functional theory calculations and electrochemical characterizations, the doping of Cu can accelerate the Volmer step and therefore strengthen the water adsorption/dissociation on the respective Ni sites and S sites during the HER process. As a result, the electrocatalyst exhibits superior and stable HER performance in both 1 M KOH and 1 M phosphate-buffered saline (PBS) solutions, with much lower overpotentials of 121 and 228 mV at a current density of 10 mA cm −2, respectively, in comparison to bare Ni3 S2 . We therefore conclude that the tailored control of the water adsorption/dissociation capability of Ni3 S2 will open significant opportunities for the rational design of alkaline and neutral electrocatalysts from earth-abundant and stable materials.